Malignant Lymphoma Presenting as Fulminant Hepatic Failure - Elizabeth Nizalik; Ekrem Zayed; Annette Foyle (Canadian Journal of Gastroenterology, 1989)
A patient with fulminant hepatic failure who had a T8 malignant lymphona is described. A review of the literature yields 11 other cases with hematologic malignancies with similar presentation. To the authors’ knowledge this is the first case in which cell marker analysis was performed. Pitfalls in morpholog1c diagnosis are discussed.